186k views
4 votes

\large \tt \: { x }^( 2 ) +  x \right^( 2 ) = 1

Solve for y. Attach a graph too.
Note :- The graph will come in the shape of a heart.

Only solve if you know it!​​

User Alqin
by
5.7k points

1 Answer

2 votes


\huge \boxed{\mathbb{QUESTION} \downarrow}


  • \large \tt \: { x }^( 2 ) +  ) \right) ^( 2 ) = 1


\large \boxed{\mathfrak{Answer \: with \: Explanation} \downarrow}


{ x }^( 2 ) +  \left( y- √( \left^( 2 ) = 1

Subtract x² from both sides of the equation.


\left(y-√(|x|)\right)^(2)+x^(2)-x^(2)=1-x^(2)

Subtracting x² from itself leaves 0.


\left(y-√(|x|)\right)^(2)=1-x^(2)

Take the square root of both sides of the equation.


y-√(|x|)=\sqrt{1-x^(2)} \\ y-√(|x|)=-\sqrt{1-x^(2)}

Subtract − √∣x∣ from both sides of the equation.


y-√(|x|)-\left(-√(|x|)\right)=\sqrt{1-x^(2)}-\left(-√(|x|)\right) \\ y-√(|x|)-\left(-√(|x| ) \right)=-\sqrt{1-x^(2)}-\left(-√(|x|)\right)

Subtracting − √∣x∣ from itself leaves 0.


y=\sqrt{1-x^(2)}-\left(-√(|x|)\right) \\ y=-\sqrt{1-x^(2)}-\left(-√(|x|)\right)

Subtract − √∣x∣from √1- x².


\underline{\underline{ \sf \: y=\sqrt{1-x^(2)}+√(|x|) }}

Subtract − √∣x∣from - √1- x².


\underline{\underline{ \sf \: y= - \sqrt{1-x^(2)}+√(|x|) }}

The equation is now solved.


\large \boxed{ \boxed{ \bf \: y=\sqrt{1-x^(2)}+√(|x|) }}\\ \\ \large\boxed {\boxed{ \bf \: y=-\sqrt{1-x^(2)}+√(|x|) }}

_________________________________

  • Refer to the attached image for the graph.

\large \tt \: { x }^( 2 ) +  \left( y- √( \left^( 2 ) = 1 Solve for y. Attach a graph-example-1
User Frank Drebin
by
5.9k points